2018
DOI: 10.1155/2018/1078547
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Human Mesenchymal Stromal Cells on Porcine Hepatocyte Viability and Albumin Secretion

Abstract: Porcine hepatocytes transplanted during acute liver failure might support metabolic functions until the diseased liver recovers its function. Here, we isolated high numbers of viable pig hepatocytes and evaluated hepatocyte functionality after encapsulation. We further investigated whether coculture and coencapsulation of hepatocytes with human multipotent mesenchymal stromal cells (MSC) are beneficial on hepatocyte function. Livers from 10 kg pigs (n = 9) were harvested, and hepatocytes were isolated from liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, they also provide a diffusive control of surrounding vasculature or tissue by the paracrine factors secreted by the encapsulated cells. Previous studies showed that MSCs in the microcapsules with porcine hepatocytes enhanced the viability and function of porcine hepatocytes [ 36 , 37 ]. Therefore, we used APA to microcapsule UMSCs with human primary hepatocytes and transplanted these microcapsules into ALF mice to observe their effects on ALF in the present study (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also provide a diffusive control of surrounding vasculature or tissue by the paracrine factors secreted by the encapsulated cells. Previous studies showed that MSCs in the microcapsules with porcine hepatocytes enhanced the viability and function of porcine hepatocytes [ 36 , 37 ]. Therefore, we used APA to microcapsule UMSCs with human primary hepatocytes and transplanted these microcapsules into ALF mice to observe their effects on ALF in the present study (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that MSCs in the microcapsules with porcine hepatocytes enhanced the viability and function of porcine hepatocytes. (36,37) .Therefore, we used APA to microcapsule UMSCs with human primary hepatocytes and transplanted these microcapsules into ALF mice to observe their effects on ALF in the present study (Fig.1C and Fig.2A). The results showed that transplantation of co-microcapsule of UMSCs and hepatocytes signi cantly attenuated liver injury, resulting in improved survival rate of LPS/D-galinduced ALF mice (Fig.2B-2E).…”
Section: Discussionmentioning
confidence: 94%
“…MSCs transplantation from the portal vein can effectively reduce the lipid accumulation and mitochondrial dysfunction after hepatectomy. The therapeutic effect of MSCs depends on paracrine cytokines, including IL-10, PGE2, and IL-6 28 . IL-10 is a cytokine that can regulate the growth and differentiation of innate immune cells 29 .…”
Section: Discussionmentioning
confidence: 99%